MYSTERY, MYTH, HISTORY: THE DIMENSIONS OF SPIRITUALITY IN THE CONTEXT OF AVATARA - Vekathanam, Mathew (Journal of Dharma, 1988)
Spirituality may be understood as man’s ’adjustment’ with the ultimate Mystery, the goal of man’s existence. It is the existence before God, the human’ spirit being grasped, sustained and transformed by the Supreme Spirit; it is man’s search for communion with God, an anticipation of the human salvation awaited in the age to come. The constant theme of spirituality is man’s being with God or God’s being with man.